What biogeography and DNA can reveal: new delimitations of Laserpitium s.l. (Apiaceae) genera and a new allied Iberian genus - González-Toral, Claudia; Sanna, Mauro; Nava, Herminio S.; Prieto, José Antonio Fernández; Cires, Eduardo (Phytotaxa, 2025)
Laserpitium s.l. (Apiaceae family) is a taxonomically complex genus comprising 13–35 herbaceous species distributed through the North Hemisphere. Molecular studies based on nuclear markers and focused on the Scandiceae tribe divided this genus into various genera and revealed that their fruit (schizocarp) morphology generated non-monophyletic groups. In this context, some Iberian subspecies of Laserpitium latifolium, Laserpitium gallicum, Thapsia nestleri, Thapsia eliasii, and Silphiodaucus prutenicus subsp. dufourianus have an unclear taxonomic status, while Laserpitium longiradium genetic adscription has not been confirmed. We aim to determine their phylogenetic position within Laserpitium s.l. and their taxonomic status based on nuclear (ITS) and plastid (rpl16, trnL and trnL–trnF) markers, carpological data and biogeographic analyses. Our topologies and biogeographic analyses only validated one of these subspecies. Nevertheless, phylogenetic relationships, niche differences and biogeographic ranges supported the division of Thapsia s.l. into three genera: Iberian-French Thapsia s.s., a new Iberian genus (formed by Thapsia nestleri, Thapsia eliasii and Laserpitium longiradium) and the Mediterranean Elaeoselinum, in which various species have been included for the first time. The Iberian Silphiodaucus prutenicus subsp. dufourianus is a separate species. Finally, overlapping carpological features within Laserpitium s.l. further supports the schizocarp homoplastic character hypothesis.